Towards Incremental FSM-based Testing of Software Product Lines - Capellari, Maykon Luís; Gimenes, Itana Maria de Souza; Simão, Adenilso da Silva; Endo, Andre Takeshi (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2012)
Software Product Line (SPL) is an approach which offers several benefits for organizations, such as significant reductions in the development and maintenance costs, reduced time-to-market, and personalized software products. In SPLs, the testing activity presents challenges due to characteristics of their development process. The cost of testing SPL is usually higher than the cost of testing traditional systems. SPLs foster the reuse of artifacts that include requirement specifications, code and models. Among different models used in an SPL, state-based models, such as Finite State Machines, are promising candidates to support the test case generation. Therefore, we propose a strategy to reuse test cases generated for different products of an SPL. Test cases are derived from Finite State Machines representing products instantiated from an SPL. The test cases generated for a product are reused when testing further products instantiated from the same SPL, in order to reduce the size of additional test cases. We illustrate our strategy in a case study using two SPLs of embedded system applications.